Hidden fairy rings and males-Genetic patterns of natural Burgundy truffle (Tuber aestivum Vittad.) populations reveal new insights into its life cycle - Staubli, Florian; Imola, Lea; Dauphin, Benjamin; Molinier, Virginie; Pfister, Stephanie; Piñuela, Yasmine; Schürz, Laura; Sproll, Ludger; Steidinger, Brian S; Stobbe, Uli; Tegel, Willy; Büntgen, Ulf; et al. (Environmental microbiology, 2022)
Burgundy truffles are heterothallic ascomycetes that grow in symbiosis with trees. Despite their esteemed belowground fruitbodies, the species' complex lifecycle is still not fully understood. Here, we present the genetic patterns in three natural Burgundy truffle populations based on genotyped fruitbodies, ascospore extracts and ectomycorrhizal root tips using microsatellites and the mating-type locus. Distinct genetic structures with high relatedness in close vicinity were found for females (forming the fruitbodies) and males (fertilizing partner as inferred from ascospore extracts), with high genotypic diversity and annual turnover of males, suggesting that ephemeral male mating partners are germinating ascospores from decaying fruitbodies. The presence of hermaphrodites and the interannual persistence of a few males suggest that persistent mycelia may sporadically also act as males. Only female or hermaphroditic individuals were detected on root tips. At one site, fruitbodies grew in a fairy ring formed by a large female individual that showed an outward growth rate of 30 cm per year, with the mycelium decaying within the ring and being fertilized by over 50 male individuals. While fairy ring structures have never been shown for truffles, the genetics of Burgundy truffle populations support a similar reproductive biology as those of other highly prized truffles.
Keywords: Symbiosis; Ascomycota; Life Cycle Stages; mužské pohlaví; Mycorrhizae; mykorhiza; zvířata; Humans; symbióza; stadia vývoje; lidé; Male; Animals